Dakwah Dan Kekuasaan (Studi Dakwah Nabi Muhammad pada Periode Madinah) - Mastori Mastori; A. Salman Maggalatung; Zenal Arifin (Jurnal Dakwah dan Komunikasi, 2021)
The concept of the relationship between da'wah and power, especially what was practiced by the Prophet Muhammad in his da'wah in the Medina period, is an important object of research. This period was the starting point of the victory of da'wah which had enormous implications for the development of Islam in its end. The results showed that preaching and power in the Medina period had very strong relations. Most Islamic law cannot be implemented without a policy of authority. Power is inspired and exercised by the direction of revelation while preaching becomes strong and effective sustained by strength. Evidently the compilation of legalities possessed by the Prophet Muhammad was obtained through the process of Bai'at I and II in Medina, the development of Islam proceeded very quickly to reach the Arabian peninsula. The success of the Prophet Muhammad's leadership in Medina in integrating da'wah and power was important to make policy foothold by state officials.